1998
DOI: 10.1172/jci1516
|View full text |Cite
|
Sign up to set email alerts
|

Matrilysin expression and function in airway epithelium.

Abstract: We report that matrilysin, a matrix metalloproteinase, is constitutively expressed in the epithelium of peribronchial glands and conducting airways in normal lung. Matrilysin expression was increased in airway epithelial cells and was induced in alveolar type II cells in cystic fibrosis. Other metalloproteinases (collagenase-1, stromelysin-1, and 92-kD gelatinase) were not produced by normal or injured lung epithelium. These observations suggest that matrilysin functions in injury-mediated responses of the lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
248
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(271 citation statements)
references
References 53 publications
16
248
0
7
Order By: Relevance
“…22 Previous studies have demonstrated a functional role of MMP-7 in repair of airway epithelial wounds in pulmonary fibrosis. 23 Specifically, MMP-7 could facilitate epithelial cell migration by losing cell-cell and cell-matrix contacts. 24 To understand the biological significance of the cirrhosis-associated MMP-7 polymorphism on cell motility, a wound-healing assay was applied.…”
Section: Resultsmentioning
confidence: 99%
“…22 Previous studies have demonstrated a functional role of MMP-7 in repair of airway epithelial wounds in pulmonary fibrosis. 23 Specifically, MMP-7 could facilitate epithelial cell migration by losing cell-cell and cell-matrix contacts. 24 To understand the biological significance of the cirrhosis-associated MMP-7 polymorphism on cell motility, a wound-healing assay was applied.…”
Section: Resultsmentioning
confidence: 99%
“…MMP7 colocalizes with E-cadherin and cleaves its extracellular domain in wounded epithelia, which results in a loosening of cell-cell attachments. In wounded Mmp7-mutant mice, epithelial cells do not migrate and E-cadherin cleavage does not occur 85 . MMP3 also functions in epidermal wound healing, as skin wounds of Mmp3-mutant mice heal more slowly than those of control mice, owing to a deficit in actin purse-string formation 86 .…”
Section: Mmp7 Is Involved In Innate Immunity and Wound Healingmentioning
confidence: 97%
“…In a complex tissue environment, like cancer, several cell types (resident, inflammatory, tumor) express several, different MMPs, and these proteinase can either promote or restrain disease or repair processes by affecting multiple and apparently opposing processes by the same cell at the same time (Coussens et al, 2002;Egeblad and Werb, 2002;Parks et al, 2004). For example, we have determined that epithelial MMP-7 is required for wound closure and generation of antimicrobial activity (Dunsmore et al, 1998;Wilson et al, 1999) (clearly beneficial functions), but it also promotes neutrophil activation, which can be damaging and lethal McGuire et al, 2003). It is likely that to effect on different processes at the same time, a cell uses distinct mechanisms to compartmentalize an MMP to different substrates.…”
Section: Significancementioning
confidence: 97%
“…However, full activation of proMMP-7 requires both a molar excess of MMP-3 and an extended incubation, suggesting MMP-3 is not an efficient activator of MMP-7 (Imai et al, 1995). Furthermore, MMP-3 is not typically co-expressed with MMP-1 (Parks, 1999;Saarialho-Kere et al, 1994) nor with MMP-7 in vivo (Dunsmore et al, 1998;Halpert et al, 1996;Rudolph-Owen et al, 1997). Second, if co-localized, the putative activating MMP may not be present in sufficient relative amounts to cleave the zymogen, particularly in a pericellular microenvironment that contain high concentrations of other or authentic substrates.…”
Section: Activation Of Prommps By Mmpsmentioning
confidence: 99%